Library and Information Science journal as a tool for continuing professional development in Malaysia: A bibliometric study - Abu Bakar, Ahmad Bakeri (Faculty of Computer Science and Information Technology, 2005)
The main focus of this paper is to look at the role of the Library and Information Science (LIS) journal as a channel for communicating innovative ideas that could be used for the continuing education of information professionals. For this purpose, the Malaysian Journal of Library and Information Science (MJLIS) was selected for an analytical assessment of its role in communicating innovative ideas. To assess if articles found in the journal constitute contents that contain innovative ideas, a method called contextual analysis was used. The results showed that LIS journals can aptly serve as a tool for communicating innovative ideas, which can be process, product or service-based. By engaging these materials, information professionals might be able to derive benefits directly or indirectly and eventually become more learned and educated.